Menerapkan Metode Imla dalam Meningkatkan Maharah Kitabah Bahasa Arab di TPQ Nurus Sha’diyyah - Al Bukhori, Sopi Fritamasari; Irvi Nurul Husna, Ade (Jurnal Riset dan Pengabdian Masyarakat, 2024)
Education is very important in Islam because seeking knowledge is mandatory for all Muslims. Maharah kitabah is one of the skills in Arabic which only focuses on one’s ability to write correctly, correctly and well in Arabic. One way to achieve Maharah Kitabah is by using the imla method. There we don’t only focus on writing, but we also pay for the correct Arabic pronunciation so that the writing is correct. Implementation is something that is rightly connected between maharah kitabah and the dictation method. Good and proper implementation will produce a good change towards the intended target. Pronunciation is good, will lead to writing in accordance with what is said.